When norms collapse: deviant behavior of the population during the war in Ukraine: A study on the impact of war on deviant behavior among the Ukrainian population and potential prevention methods through psychological correction and social programs - Rusanov, Volodymyr (Psychosomatic Medicine and General Practice, 2024)
In the article "Deviant Behavior of the Population During the War in Ukraine," the socio-psychological consequences of the war for the country’s citizens are explored. Specifically, the impact of combat operations and constant stress on the population’s behavior is analyzed, highlighting the increase in aggression, crime, substance abuse, suicidal tendencies, and looting. Special attention is given to the role of the media in shaping a negative emotional background and exacerbating deviant behavior. Methods of psychological correction are considered, as well as the application of the international mhGAP intervention guide to provide psychosocial assistance in situations with limited access to psychiatric services.